Child labour and human rights : making children matter - Weston, Burns H. (ed.) (New Delhi, 2007)
Child Labor and Human Rights provides a comprehensive overview of the phenomenon of child labor from a human rights perspective. This book is an indispensable contribution to the growing effort to abolish abusive and exploitative child labor practices. The genesis of this book lies in a thought-provoking lecture on child labor and human rights by US senator Tom Harkin of Iowa on the occasion of The University of Iowa's commemoration of the fiftieth anniversary of the 1948 Universal Declaration of Human Rights on the eve, not coincidentally, of the adoption of the 1999 ILO Convention (No. 182) Concerning the Prohibition and Immediate Action for the Elimination of the Worst Forms of Child Labor (see appendix), now ratified by more than 155 countries. It lies also in Senator Harkin's subsequent gracious help, despite some disagreement between us re garding the suitability of children in the workplace, in securing generous con gressional funding to make possible this and related research on child labor* under my stewardship at The University of Iowa Center for Human Rights (UICHR) (see http://www.uichr.org), which I then directed. What greater proof of commitment and decency in the cause of human rights does one need? I thank Senator Harkin for his stimulating words and unqualified support. The re sult is a work, intended for teacher, student, government official, international civil servant, nongovernmental activist, and concerned citizen alike, conceived and executed in an intellectually free, multidisciplinary, and robustly open ended way.
Keywords: Child labour